DNA barcoding of razor clam Solen spp. (Solinidae, Bivalva) in Indonesian beaches - ninis trisyani margono; DWI ANGGOROWATI RAHAYU (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Trisyani N, Rahayu DA. 2020. DNA barcoding of razor clam Solen spp. (Solinidae, Bivalva) in Indonesian beaches. Biodiversitas 21: 478-484. Solen spp. are shells with various morphological characteristics with a wide distribution of tropical and subtropical beaches, including Indonesia. The identification of Solen spp. is generally based on its morphological characteristics. This method is very problematic due to specimens share similarity in morphology and color. This study was using DNA barcode as a molecular identification tool. The bivalve COI sequence was amplified using PCR and molecular phylogenetic analysis using the Neighbor-Joining method. The amplified COI gene has a length of about 665 bp. The purpose of this study was to evaluate genetic variation and compare the phylogenetic Solen spp. in Indonesian waters. The composition of the nucleotide bases of Solen spp. the comparative species are A = 26.79%, C = 23.16%, G = 19.17% and T = 30.93%. The total nucleotide base A + T was 57.72%, while G + C was 42.33%. The results of phylogenetic analysis showed that Solen spp. Cirebon and Jambi are in one clade with Solen regularis with genetic distance 0.000 - 0.002. Solen spp. Surabaya, Bangkalan, Pamekasan, and Sumenep are in separate clades and are related to Solen grandis, Solen stricus and Solen lamarckii with genetic distance from 0.146 - 0.156. The diversity of nucleotide was 0.9780 and was divided into 12 haplotypes.